Studies in Philology: tomo 45 (1948), tomo 46 (1949), tomo 47 (1950), tomo 48 (1951), tomo 49 (1952). - Alatorre, Antonio (Nueva Revista de Filología Hispánica (NRFH), 1957)
Se reseñó: Studies in Philology: tomo 45 (1948), tomo 46 (1949), tomo 47 (1950), tomo 48 (1951), tomo 49 (1952).